HUBUNGAN CARA PEMBERIAN SUSU FORMULA TERHADAP KEJADIAN KARIES GIGI PADA ANAK PRASEKOLAH DI PENDIDIKAN ANAK USIA DINI (paud) WIDYA SUARA Br. GELIMPANG, DESA SUKAWATI GIANYAR TAHUN 2013. - Ni Nengah Sumerti; I Nyoman Wirata (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2013)
Presschool children is one of the groups vurnerable vurnerable to dental caries, because at this age children have behaviour or less self supporting habits on dental health. Using bottled formula milk comsumtion influence the occurence of caries, because dairy product contain carbohidrates which is a good medium for germs acid formtion. This situation will facillate the formation of plaque which is the main cause of caries and periodontaldisease. This study to determine the relationship of how formula feeding on the incidence of dental caries in presschool children in Early Childhood (ECD) Sound Widya Br. Gelumpang Village of Sukawati Gianyar. This study of descriptive, cross sectional design. The study subject were 61 children and 61 parents/guardian of children in early chilhood Widya Sound. The result caries picture and how formula feeding in presschool children in Early Childhood Education (ECD) Sound Widya Br. Gelumpang Village of Sukawati Gianyar in 2013 most of the kids who drink formula eldest suffer dental caries. Frequency of children who drink formula using bottles, pacifier have as many as 292 prequency of dental caries (64,5%) while children who drank a glass of milk formula with as many as 161 teeth frequency of dental caries (35.5%). Resulth of bivariate statistical test with chi-squere test showed a significant correlation values. This study is a descriptive, with p=0.025 with limit values of 2.18 to convident interval. Furthermore it can be suggested : ECD Officer to inform the parent/guardian for children who suffer from dental caries that dental checups to the nearest health center. Vote early chilehood Widya expected to cooperative with the health center 1 Sukawati to hold counseling for parents of children in particular a bout the maintenance of oral health in children who drink formula.